Implikasi terhadap Pengembangan Pendidikan Modern - Muh Faisal M; Abdullah Sinring; Syamsu Kamaruddin; Mukhtar Mas'ud (DIDAKTIKA, 2024)
The concept of truth plays an important role in shaping the philosophy and practice of education. This research explores scientific and non-scientific theories of truth in the philosophy of education, analyzing their implications for contemporary education systems. Using qualitative methods and a hermeneutic approach, this research highlights coherence, correspondence, and pragmatic theories, as well as non-scientific approaches such as spiritual and cultural truths. The research results indicate the need for an integrative educational framework that respects scientific rigor while also acknowledging diverse cultural and spiritual perspectives. This research contributes to the creation of a balanced education system that meets both global and local needs.